Transmission Characteristic Analysis of Circular Arc Tooth Trace Cylindrical Gear with Considering Eccentricity Error - Dengqiu Ma; Changguo Yan; Xu Zhang; Fangzhou Chen; Zhenhuan Ye; Juan Fu; Xue Wang (Jixie chuandong)
Based on the status that the research of the influence of eccentricity error on the meshing performance of the circular arc tooth trace cylindrical gear is relatively rare， the characteristics of the circular arc tooth trace cylindrical gear processed by different processing techniques are introduced. A three-dimensional model of the circular arc tooth trace cylindrical gear with geometric eccentricity is established. By using the commercial software Adams， the dynamics simulation model of the circular arc tooth trace cylindrical gear considering eccentricity error is established to study the speed fluctuation characteristics of driven wheel in the circular arc tooth trace cylindrical gear system under three working conditions of driving system， namely， the existence eccentricity of driving wheel， the existence eccentricity of driven wheel and the common eccentricity of driven and driven wheel. The research results show that， under the 3 kinds of eccentric conditions， the speed fluctuation characteristics of driven wheel periodically changes in the circular arc tooth trace cylindrical gear system， and the eccentricity has a certain effect on the speed fluctuation characteristics. The research results provide a theoretical basis for lubrication， fault diagnosis and tooth profile modification of the CATT cylindrical gear system.